The Effect of Using Ordinary Lights and Petromak Lights in Hands Fishing Tools on the Types of Catches in Simeulue Waters - Nanda Rizki Purnama; Rianjuanda Rianjuanda; Alga Armansyah; Edy Miswar; Chaliluddin Chaliluddin; Kavinta Melanie (Jurnal Kelautan dan Perikanan Indonesia, 2023)
The development of hand line fisheries has not experienced much significant progress when compared to other fishing gear. The effectiveness of handline is determined by its design and construction, operation does not require large capital, handline fishing also uses aids such as bait and FADs. The use of light in handline fishing gear to attract phototactic fish. The research objectives were to determine the type and weight of fish caught on handline fishing gear using two different types of lights and to determine the effect of regular light and petromax on fish caught using handline fishing gear in Simeulue Waters. The research was carried out in October 2022, in Simeulue Waters, Simeulue Regency, East Simeulue District, Sinabang City. The types of data collected in this study were primary and secondary data obtained from experimental fishing methods. The effect of giving light to the catch in hand line fishing gear can be known by the data obtained from direct observation data. The weight of fish caught using ordinary lamps is at least 1840 grams and the maximum weight is 9460 grams, while using petromax lamps the fish weighs at least 1330 kg and the largest catch is 9490 kg. The research results showed that there were no differences that had a significant effect on hand line catches, so do a statistical analysis using the t test with the result -.161.Keywords: catch, hand line, light, Simeulue